E-Module Based on Blended Learning Type Flipped Classroom on Climate Change Materials to Train Students' Digital Literacy Ability - Anik Mufidah; Sifak Indana; Imam Supardi Zainul Arifin (Indonesia Emerging Literacy Education, 2023)
Objective: E-modules are teaching materials integrated with technological advances using digital applications that are more attractive to students. One of the problems in learning science is the low ability of students' digital literacy. Efforts to increase digital literacy skills include using an e-module based on a flipped classroom type of blended learning. This study aims to describe the validity of teaching materials consisting of syllabi, lesson plans, student worksheets, blended learning-based flipped classroom-type e-modules on climate change material, digital literacy ability questionnaires, and knowledge test instruments. Method: The method used in this research is limited to the validity of teaching materials. The developed teaching materials were tested on students of class VII JHS. Data collection was carried out using the validation method, and data analysis was carried out quantitatively. Results: The results of the data analysis concluded that the syllabus was in the very valid category, the lesson plans were in the valid category, the e-module was in the valid category, the student worksheets were in the valid category, the digital literacy ability questionnaire sheet was in the valid category, and the knowledge test instrument was in the valid category. Novelty: Flipped classroom-based blended learning-based e-modules can be used as an alternative to electronic modules in learning to improve students' digital literacy skills. This e-module can be used for varied learning both online and offline so that students are expected to gain learning experiences that can later be used to solve problems encountered in real life.